Seismic efficiency of self-centering braced frame under near-field pulse-like ground motions - نوید رهگذر; aboreza sarvghad moghadam; آرمین عظیمی نژاد (مجله مدل سازی در مهندسی, 2018)
This research investigates the efficiency of the self-centering steel braced frame equipped with replaceable yielding fuses and post-tensioning cables subjected to far-field records and near-field pulse-like ground motions. For this purpose, engineering seismic demand parameters for tewelve self-centering steel braced frames under far-field ground motions are compared with those for near-field ground motions.The braced frames are different from seismic frame type, seismic site location, and the number of stories. The self-centering braced frames are designed using a limit-state design procedure and are simulated in OpenSees software. Nonlinear dynamic time-history analyses are conducted under design earthquake , DBE , level and maximum considerable earthquake , MCE , level. Findings demonstrate that the self-centering steel braced frames are capable of mitigating seismic damage under both near -field pulse - like and far - field ground motions, which are provided by features such as rocking behavior, re-centering action, and directing damage ability .